Against the Current: Selected Writings 1939 - 1996 - Trudeau P. E.; Trudeau Pierre Elliott; Pelletier Gerard (Toronto McClelland & Stewart, 1996)
Gerard Pelletier has brought together a wide variety of excerpts and articles to make up this collection. It includes representative pieces from Trudeaus youth, selections from previously published books and journals, as well as speeches, interviews, letters written to newspapers, and classic essays from his time as a founding contributor to the magazine Cite libre. From beginning to end, whether writing about Utopia or the constitutional compromises wrought by his political opponents, Trudeau demonstrates that he has had no equal, counterpart, or successor in Canadian public life.
Keywords: 32